Fractionating proteins with nitrite-reducing activity in “Candidatus Kuenenia stuttgartiensis” strain CSTR1 - Ude, Emea Okorafor; Sure, Pranathi; Rimjhim, Rimjhim; Adrian, Lorenz; Ding, Chang (Frontiers in Microbiology, 2025)
The anammox bacteria “Candidatus Kuenenia stuttgartiensis” (Ca. Kuenenia) are able to gain energy by combining ammonium and nitrite to produce nitrogen gas, which is an ecologically and technically significant activity process. In this reaction, nitric oxide serves as a recognized intermediate in the reduction of nitrite, which is subsequently combined with ammonium to produce hydrazine. However, the enzyme that converts nitrite to nitric oxide remains elusive. In this study, we investigated the nitrite-reducing activity in “Ca. Kuenenia stuttgartiensis” strain CSTR1 to identify candidates for such an enzyme. An optimized in vitro assay was established to measure nitrite-reducing activities, with which we followed the activity in protein fractions obtained from various fractionation methods. Separation of the cell extract of strain CSTR1 with size exclusion chromatography yielded active fractions corresponding to a molecular size range of 150–200 kDa. Several proteins coeluted with the nitrite-reducing activity, including the hydroxylamine dehydrogenase HOX, an NADP-dependent isopropanol dehydrogenase (Adh), an electron-transfer 4Fe-4S subunit protein (Fcp), and a nitric oxide detoxifying flavorubredoxin (NorVW). However, further separation of the cell extract with anion exchange chromatography, resulted in much lower activity yields, and activities were distributed among several fractions. In addition, fractionation of cell extracts using ultracentrifugation and ultrafiltration linked the activity to HOX, but could not exclude the involvement of other proteins in the activity. Overall, our results suggest that the molecular mechanism for nitrite reduction in “Ca. Kuenenia” strains is more complex than that currently described in the literature. Nitrite reduction appears to be strongly associated with HOX but may additionally require the participation of other proteins.